Ashermanʼs syndrome: a clinical case report and review of the literature - Bužinskienė, Diana; Drąsutienė, Gražina; Zdanytė, Kristina (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English] Intrauterine adhesions – formation of the connective tissue in uterine cavity. It leads to endometrial dysfunction and partial or complete obliteration of the uterine cavity and/or the cervical canal, resulting in conditions such as menstrual cycle disorders (hypomenorrhea, dysmenorrhea or amenorrhea), infertility, recurrent pregnancy loss, etc. When the clinical symptoms occur the condition is called Asherman’s syndrome. We represent a case report of a 30 years old woman (gravida 1, para 0, abortus 1) with infertility lasting for two years. The patient had no other complaints. According to the patient, she underwent an abortion two years ago in order to terminate the pregnancy of 8 weeks. Transvaginal (2D) sonoscopy showed no alterations in uterine cavity. Intrauterine adhesions were first diagnosed with hydrosonoscopy, followed by HyFoSy (Hysterosalpingo Foam Sonography) and hysteroscopy with performed adhesiolysis. Postoperative period was normal. Two months after the surgery the patient was diagnosed with pregnancy. The pregnancy was normal, Caesarean delivery was performed for a healthy baby boy with Apgar 9/10. Direct damage to endometrium plays the main role in formation of intrauterine adhesions. There are four classifications available to evaluate the difficulty of treatment and the risk of complications, as well as to assess the reproductive outcome after the surgery. In order to diagnose intrauterine adhesions one should always do transvaginal ultrasound examination or hydrosonography, hysterosalpingography or hysterosalpingosonography and hysteroscopy. The main guidelines to treatment: diagnostic hysteroscopy, hysteroscopic adhesiolysis with insertion of balloon catheter or intrauterine device or hyaluronic acid or SprayGel, postoperative hormonal therapy and, if needed, assisted reproductive technology. Stem cells transplantation into uterine cavity showed a positive results in treating Asherman’s syndrome and could be a future therapy option. Pregnancy after the treatment of Asherman’s syndrome must always be classified as a high risk pregnancy.